Penggunaan Bahasa Indonesia yang Baik dan Benar (Sintaksis dan Semantik) sebagai Kaidah Bahasa Indonesia serta Analisis Kesalahan Berbahasa Indonesia - Wisrayani Wisrayani; Rahma Ashari Hamzah; Shalsa Nurfitriana (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze the proper and correct use of Indonesian, focusing on syntactic and semantic aspects, as well as identifying language errors that are common among speakers. As the national language, Indonesian has a significant role in education, communication, and culture. However, there are still various challenges in its mastery and application, especially at the elementary school level. The method used in this research is a descriptive qualitative approach, with data collection techniques through observation of written documents, interviews with language experts, and literature studies. The data obtained will be analyzed using a thematic approach to identify patterns of language errors and the factors that cause them. The results show that errors in language use often occur in syntactic structures, including phrases, clauses, and sentences, as well as in semantic aspects related to understanding meaning. Most of these errors are caused by a lack of understanding of grammar rules and weak language teaching at the primary school level. This study recommends strategies to improve the quality of Indonesian language learning through the development of more effective teaching methods, which are based on the analysis of language errors. It is hoped that the findings can contribute to the improvement of students' language competence as well as to the improvement of the quality of Indonesian language learning.